ENDOWMENT FUNDS AS A FORM OF IMPLEMENTATION OF PUBLIC-PRIVATE PARTNERSHIP IN HIGHER EDUCATION: FOREIGN EXPERIENCE - Z. Aubakirova; Z. T. Beisenbayev; M. Zh. Zhaparova (Экономика: стратегия и практика)
This article examines the foreign practice of public-private partnership in the higher education system, describes the importance of endowment funds as a mechanism of financing in higher education. In world practice, endowment funds demonstrate the possibility of a significant reduction in the share of public funding for education, along with an improvement in the quality of services provided. Noted causes the need to develop and implement forms of public-private partnership that promote mutually beneficial cooperation between government and business, improving the mechanism public-private partnerships that will ultimately contribute to the successful socio-economic development of the state and business.